Promosi Kesehatan Pada Kader Kesehatan Untuk Pencegahan Kekambuhan Pada Pasien Pasca Pasung - Susilawati, Ari; , Arif Widodo, A.Kep., M.Kes (2017)
Mental health in Indonesia was still not a priority agenda. This was evident from the low government investment in health and community awareness of mental health and community empowerment has not been adequate. Though their autonomy enables local governments to improve mental health in its territory. The role of health workers in maintaining quality public health was very important. Increasing the role of health workers, especially in the field of mental health really needs to be improved, because of the low participation of health cadres in maintaining the quality of community mental health. This study aims to determine the effect of health promotion in the health cadre for the prevention of recurrence in patients with post stocks. This research was a form of pre-experimental with one group pre test and post test design. The study population are all health workers in the district Jatinom Klaten district in whose territory the stocks that are patients post Kledokan village, Grail, Suran, Jetis, Krajan and Sweet Orange with the number of cadres as many as 34 people. The research sample as many as 34 cadres with total sampling technique. The collection of research data using a questionnaire and analyzed using t-test. The results showed test results paired sample t-test knowledge before and after health promotion obtained tcount of 5.708 (p-value) 0,000 so H0 was rejected. While the results of paired samples t-test attitudes before and after health promotion obtained tcount of 9.936 (p-value) 0,000 so H0 was rejected. Conclusion The study shows the provision of health promotion proved effective against the increase in knowledge and attitudes about mental illness recurrence prevention in health cadres in Puskesmas Jatinom Klaten.